The Assessment of Risk Factors for Work Safety at the Workplace for Driver - Beatrice Daniela TUDOR (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2019)
In this is paper present the calculation of the overall risk level for workplace - driver. Risk assessment is the first step towards safer and healthier jobs, and it is the way to reduce accidents at work and occupational diseases. The new trends in managing an organization are to consider as performing an organization that is equally concerned with improving the quality of products / services and increasing economic efficiency, as well as providing adequate working conditions for employees and environmental protection environment, by increasing the quality of life in general. All of these components are addressed within integrated management systems, which usually aim to organize the operation of companies. Employee health and safety, protection of neighbouring populations, flora and fauna, water and soil are just as important as the organization's profit. But what does the health and safety component of work in this integrated system involve? The increase in profit results from the reduction of material losses due to accidents and damages, the reduction of absenteeism due to medical leave, the elimination of losses caused by penalties resulting from non-compliance with legal requirements, etc.